2021
DOI: 10.1021/jacs.1c10200
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for Antibacterial Discovery and Development

Abstract: The rising prevalence of multidrug-resistant bacteria is an urgent health crisis that can only be countered through renewed investment in the discovery and development of antibiotics. There is no panacea for the antibacterial resistance crisis; instead, a multifaceted approach is called for. In this Perspective we make the case that, in the face of evolving clinical needs and enabling technologies, numerous validated antibacterial targets and associated lead molecules deserve a second look. At the same time, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 132 publications
0
53
0
Order By: Relevance
“…The rising prevalence of resistant bacteria is an urgent health crisis which can only be countered through renewed investment in the discovery and development of new antibacterial drugs. 25 In this work, a series of novel amphiphilic AMPs were designed and synthesized based on the biological characteristics of most natural AMPs (such as the positive charge, amphiphilicity, helicity). The antimicrobial activity, hemolysis and cytotoxicity assays showed that the LP21 lipopeptide showed the strongest antimicrobial effect, low hemolysis and cytotoxicity, and still exhibited enough antibacterial activity in the serum, which endowed LP21 with good drug properties.…”
Section: Discussionmentioning
confidence: 99%
“…The rising prevalence of resistant bacteria is an urgent health crisis which can only be countered through renewed investment in the discovery and development of new antibacterial drugs. 25 In this work, a series of novel amphiphilic AMPs were designed and synthesized based on the biological characteristics of most natural AMPs (such as the positive charge, amphiphilicity, helicity). The antimicrobial activity, hemolysis and cytotoxicity assays showed that the LP21 lipopeptide showed the strongest antimicrobial effect, low hemolysis and cytotoxicity, and still exhibited enough antibacterial activity in the serum, which endowed LP21 with good drug properties.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the development of antibacterial materials that are not prone to drug resistance is of great significance to ensure food safety and human health. [1][2][3][4][5][6] and 1180 nm (g-factor = 0.033). The chiral Co SS exhibited obvious chiral optical activity and paramagnetic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the development of antibacterial materials that are not prone to drug resistance is of great significance to ensure food safety and human health. [ 1–6 ]…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Further, the lack of accurate diagnosis and effective treatment strategies for bacterial infection in clinical settings is an important reason for the sharp rise in bacterial drug resistance. [6][7][8] To address this challenge, the development of advanced, accurate diagnostic methods and efficient anti-bacterial treatment strategies are needed. 9,10 Common traditional detection techniques for diagnosing bacterial infections in clinical settings, which include positron emission tomography 11 and radioactive labeling, 12 lack sufficient resolution and practicality.…”
Section: Introductionmentioning
confidence: 99%
“…3–5 Further, the lack of accurate diagnosis and effective treatment strategies for bacterial infection in clinical settings is an important reason for the sharp rise in bacterial drug resistance. 6–8 To address this challenge, the development of advanced, accurate diagnostic methods and efficient anti-bacterial treatment strategies are needed. 9,10…”
Section: Introductionmentioning
confidence: 99%